The Role of Financial Education in Improving Personal Financial Planning: A Qualitative Study on Generation Z - KMT Lasmiatun (PT. Anagata Sembagi Education, 2024)
Generation Z has grown up in the digital age with extensive access to information, yet they often lack adequate knowledge on personal financial management. Low financial literacy can lead to poor financial decisions and financial problems in the future. The main objective is to understand how financial education helps Generation Z to improve their personal financial planning. The main objective is to understand how financial education affects Generation Z's financial awareness, knowledge and behavior. A qualitative approach was used in this research with a case study method. Data was collected through in-depth interviews with purposively selected Generation Z individuals. The interviews were analyzed using thematic analysis method to identify emerging patterns and themes. The results show that financial education has a significant role in improving Generation Z awareness and personal financial planning skills. Participants who have received financial education demonstrate better knowledge of financial management, as well as have more positive financial behaviors such as saving, investing and spending management habits. These findings provide important insights for policymakers, educational institutions and the private sector in designing and implementing effective financial education programs. More comprehensive and accessible financial education is needed to ensure Generation Z can make better financial decisions and manage personal finances more effectively.